Assessing the Economic Impact of Service Quality on Customer Satisfaction, Trust, and Loyalty in Lion Air Indonesia - Linardy, Regina Fortunata; Berlianto, Margaretha Pink (Yayasan Riset dan Pengembangan Intelektual, 2025)
Air transportation is an efficient mode of travel for covering long distances in a short period, and currently, more options are available to the public through various airlines. One of the dominant airlines in Indonesia’s domestic market is Lion Air, with a market share reaching 29.7% in 2021. However, despite its large sales volume, Lion Air frequently faces criticism regarding the quality of service provided to customers. This study aims to analyze the influence of factors such as reliability, assurance, responsiveness, facilities, and employees on customer satisfaction, customer trust, and customer loyalty in Lion Air. The respondents of this research are 137 customers who have used Lion Air services for domestic flights. The data obtained were analyzed using Smart PLS 3 to test the structural model and hypotheses. The results show that assurance and employee variables have a significant effect on customer satisfaction. Furthermore, customer satisfaction has a significant and positive impact on customer trust and customer loyalty. This indicates that good assurance and employee factors can increase customer satisfaction, which in turn influences trust and loyalty toward Lion Air. Therefore, Lion Air needs to improve performance in these two variables to enhance customer satisfaction, ultimately affecting customer loyalty.